2023
DOI: 10.3390/en16020634
|View full text |Cite
|
Sign up to set email alerts
|

A Review of State Estimation Techniques for Grid-Connected PMSG-Based Wind Turbine Systems

Abstract: The power system network grows yearly with a large number of nonlinear power generation systems. In this scenario, accurate modeling, control, and monitoring of interface systems and energy conversion systems are critical to the reliability and performance of the overall power system. In this trend, the permanent magnet synchronous generator (PMSG)-based wind turbine systems (WTS) equipped with a full-rated converter significantly contribute to the development of new and renewable energy generation. The variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Due to the advantages it provides, it is the fastest-developing energy resource in terms of installed power [9]. One of the clean RER that is found in great amounts in all parts of the world, that is cost-efficient, and that is the most efficient in commercial terms is wind power [10][11][12]. Wind power is one of the most significant RER that shows the fastest development with its technology and usage, and it is able to compete with conventional energy resources with its economy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages it provides, it is the fastest-developing energy resource in terms of installed power [9]. One of the clean RER that is found in great amounts in all parts of the world, that is cost-efficient, and that is the most efficient in commercial terms is wind power [10][11][12]. Wind power is one of the most significant RER that shows the fastest development with its technology and usage, and it is able to compete with conventional energy resources with its economy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [24], a review of advanced methods of wind turbine estimation, electricity generation, and nonlinear modeling has been done, so that the wind turbine can produce the energy it needs with goals such as the greatest efficiency. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive overall control in the whole wind speed range increases the robustness of the DPMSG-based WPS [13]. The modeling and control methods of the DPMSG-based WPS are compared and analyzed, and the direction of future research is demonstrated in [14].…”
Section: Introductionmentioning
confidence: 99%